Microscopic study on colonization and antimicrobial property of endophytic bacteria associated with ethnomedicinal plants of Meghalaya. Issue 3 (September 2017) - Nongkhlaw, Fenella Mary War; Joshi, S.R.
Abstract: Microscopic visualization using transmission electron microscopy (TEM) can provide a better understanding of endophytic colonization within ethnomedicinal plants. Bacterial endophytes were found attached to the host cell wall colonizing the aerenchyma and intercellular spaces of the epidermis and outer cortex except the vascular system. Colonization was non-uniform as single cells, doublets or in the form of microcolonies. Analysis of in vivo antibacterial action of the methanolic extracts of the isolated endophytic bacteria against Gram-positive, Streptococcus pyogenes MTCC 1925 and Gram-negative, Salmonella enterica ser. paratyphi MTCC735 pathogens has revealed the morphological damages in the tested pathogens respectively, under scanning electron microscopy (SEM). Detached cell wall and cell burst were observed in Streptococcus pyogenes where as, cell blisters were shown in Salmonella enterica ser. paratyphi. The study on bacterial endophyte colonization process is important to better predict how endophytes interact with their host and establish themselves in the plant environment by procuring biocontrol activity.